Genotype×Environment Interactions and Stability for Grain Yield and its Components in WBPH Tolerant Rice (Oryza sativa L.) Genotypes - Prajapati, K. N.; Kathiria, K. B. (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted during kharif, 2013–2015 with three different seasons at Main Rice Research Station, Anand Agricultural University, Nawagam, Gujarat. The stability analysis was carried out to study genotype x environment interaction for grain yield per plant. Analysis of stability parameters revealed that the mean squares due to genotypes were significant for all the characters. However, variances for environments were significant for all the characters studied except plant height and hulling per cent revealed that environment differ from season to season. The mean sums of squares for genotype×environment interactions in pooled analysis were found significant only for grain yield per plant. This suggested that the genotypes under study had reacted differently to the environments for grain yield per plant and remaining characters showed non-significant mean squares indicated that environment had little effects on the expression of those characters. Based on stability parameter for grain yield per plant, genotypes viz., IR 71700-247-1-1-2, IR 13146-45-2-3, IR 04A 395, IR 09A 102, IR 09N 190, IR 10A 110, IR 78581-12-3-2-2, GAR 13 and Gurjari were identified as stable genotypes with average stability and wider general adaptability over the environments. While, IR 02A 585, IR 77334-99-2-3-2 and IR 09A 104 were identified stable for favorable environments.